Build the expressway for the salt-tolerant anammox process: Acclimation strategy tells the story. (1st January 2021) - Zhang, Quan; Fu, Jin-Jin; Wu, Qing-Yuan; Chen, Jin-Yan; Fan, Nian-Si; Huang, Bao-Cheng; Jin, Ren-Cun
Abstract: The wide existence of saline wastewater has attracted public attention due to its environmental destructiveness. The potential of anammox to treat saline wastewater was systematically evaluated in this study. Three bioreactors with different salinity increasing strategies (R1 : inhibition kinetic; R2 : gradient increasing; R3 : pulsed increasing) were operated to identify the optimal acclimation mode. The results showed that the inhibition of anammox activity by salinity was mainly caused by the loss of enzyme activity. Under the condition of 25.0 g NaCl L −1, the highest nitrogen removal rate of R3 (2.36 ± 0.14 kg N m −3 d −1 ) indicated that the pulsed strategy might be optimal. Changes in microbial community might be the primary reason lead to different acclimatization results. The relative abundance of anammox bacteria increased by 37.19% in R1 and by 46.81% in R3, but remained stable in R2 with increasing salinity. Dynamic varations in bacterial interactions, proteins, and functional genes revealed the potential resistance mechanisms of bacteria to salinity. The present work provides a novel approach and guidance for the treatment of nitrogen-rich saline wastewater by the anammox process. Graphical abstract: Image 1 Highlights: Three acclimation strategies for salt-tolerant anammox process were proposed for the first time. The inhibition of FAB by salinity was mainly caused by the loss of enzyme activity. High abundance of anammox bacteria led to the excellent acclimatization results. Corresponding strategies can be selected based on the wastewater characteristics.